Analisis Margin Saluran Pemasaran Hasil Tangkapan Nelayan Soma Pajeko di Desa Tumbak Kecamatan Pusomaen Kabupaten Minahasa Tenggara - Sambouw, Kevin R.; Sondakh, Srie J.; Suhaeni, Siti; Pangemanan, Jeannette F.; Rantung, Steelma V.; Tambani, Grace O. (Universitas Sam Ratulangi, 2024)
Abstract Tumbak Village is one of the coastal villages in Pusomaen District, Southeast Minahasa Regency. Most of the people of Tumbak Village work as fishermen, one of the fishing gear used by fishermen in Tumbak Village is Soma pajeko which is the term for purse seine. The objectives of the study were (1) to find out the number of marketing channels for the catches of soma pajeko fishermen in Tumbak Village, (2) to find out the marketing margin for the catches of soma pajeko fishermen in Tumbak Village. The basic method that will be used in this study is a survey. The population in this study are fishermen who own soma pajeko in Tumbak Village and the traders who market them. Data collection used Snowball Sampling with a sample size of 13 people. The data collected consisted of primary data and secondary data. Data collection was carried out through observation, documentation and interviews guided by a questionnaire. The data obtained were analyzed descriptively qualitatively and quantitatively Based on the results of the study, it is known that the marketing channels for the catches of Soma Pajeko fishermen in Tumbak Village are only two marketing channels, namely: from fishermen to intermediary traders to retailers and finally to consumers; from fishermen to retailers directly to consumers. The results of the margin analysis carried out on the two marketing channels for fish caught by Soma Pajeko fishermen in Tumbak Village showed that the marketing margin on both marketing channels was the same, namely IDR 10,000 or 47.62%. The length of the marketing channel for fish caught by fishermen in Tumbak Village does not affect the level of income of fishermen, but it greatly affects the profits of traders. The shorter the marketing channel, the more profitable it is for retailers, but the margin or price difference received by fishermen and paid by consumers remains the same, namely IDR 10,000. Keywords: marketing; marketing system; Tumbak Village Abstrak Desa Tumbak merupakan salah satu desapesisir yang ada di Kecamatan Pusomaen Kabupaten Minahasa Tenggara. Masyarakat Desa Tumbak sebagian besar memiliki mata pencaharian sebagai nelayan,salah satu alat tangkap yang digunakan nelayan Desa Tumbak adalah Soma pajeko yang merupakan istilah pukat cincin atau purse seine. Tujuan penelitian adalah (1) Mengetahui banyaknya rantai saluran pemasaran hasil tangkapan nelayan soma pajeko yang ada di Desa Tumbak, (2) Mengetahui Margin pemasaran hasil tangkapan nelayan soma pajeko yang ada di Desa Tumbak. Metode dasar yang akan digunakan dalam penelitian ini yaitu survei. Popolasi dalam penelian ini adalah nelayan pemilik soma pajeko di Desa Tumbak dan para pedagang yang memasarkannya. Pengambilan data menggunakan Snowball Sampling dengan jumah sampel 13 orang. Data yang dikumpulkan terdiri dari data primer dan data sekunder. Pengumpulan data dilakukan melalui observasi, dokumentasi dan wawancara yang dipandu dengan kuesioner. Data yang diperoleh dianalisis secara deskriptif kualitatif dan kuantitatif Berdasarkan hasil penelitian diketahui bahwa saluran pemasaran hasil tangkapan nelayan Soma Pajeko di Desa Tumbak hanya ada dua saluran pemasaran yaitu: dari nelayan ke pedagang perantara ke pedagang pengecer terakhir ke konsumen; dari nelayan ke pedagang pengecer langsung ke konsumen. Hasil analisis margin yang dilakukan pada kedua saluran pemasaran ikan hasil tangkapan nelayan soma pajeko di Desa Tumbak diketahui bahwa margin pemasaran pada kedua saluran pemasaran itu sama yaitu Rp10.000 atau 47,62%. Panjang pendeknya saluran pemasaran ikan hasil tangkapan nelayan di Desa Tumbak tidak mempengaruhi tingkat pendapatan nelayan, namun sangat berpengaruh terhadap keuntungan para pedagang. Semakin pendek saluran pemasaran semakin menguntungkan bagi pedagang pengecer, namun margin atau beda harga yang diterima nelayan dengan yang dibayarkan konsumen tetap sama yaitu Rp10.000. Kata kunci: pemasaran; sistem pemasaran; Desa Tumbak